The Aceh Tamiang Regency Government’s Public Relations Crisis Communication Strategy for Restoring Its Public Image Following the Flood Disaster: English - syarifah ismaraynita; sigit hardiyanto (Indonesian Journal of Communication and Social, 2026)
This study aims to analyze the crisis communication strategies implemented by the Public Relations Office of the Aceh Tamiang Regency Government in restoring its public image following the 2025 flood disaster. The hydrometeorological disaster caused physical damage, communication disruptions, and a crisis of public trust in the local government due to delays in aid distribution and a lack of information provided to the public. This study employs a descriptive qualitative approach using the Situational Crisis Communication Theory (SCCT) as its analytical framework. Research data were collected through in-depth interviews, observations, and documentation of the communication activities of the Aceh Tamiang Regency Government’s Public Relations Office. Research informants consisted of the Head of the Public Relations Division and disaster-affected residents selected using purposive sampling. Data analysis employed the Miles and Huberman model through data reduction, data presentation, and drawing conclusions. The results indicate that the Public Relations Office of the Aceh Tamiang Regency Government implemented crisis communication strategies specifically the diminish strategy, rebuild strategy, and bolstering strategy through information clarification, the use of social media, the establishment of a media center, and the publication of recovery efforts and humanitarian aid activities. These strategies have helped rebuild public trust, although challenges remain, such as limited communication networks and public dissatisfaction with the distribution of aid.